1995
DOI: 10.1002/pd.1970150208
|View full text |Cite
|
Sign up to set email alerts
|

The development of the fetal eye: In utero ultrasonographic measurements of the vitreous and lens

Abstract: Our objective was to establish nomograms for fetal eye measurements from 12 weeks' gestation by using transvaginal and transabdominal high-resolution ultrasound techniques. A prospective cross-sectional study was performed on 450 normal singleton pregnancies between 12 and 37 weeks' gestation. Vitreous and lens circumferences were measured by transvaginal ultrasonography until 17 weeks, and by abdominal ultrasound between 18 and 37 weeks' gestation. Regression analyses were used to create nomograms, and severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 5 publications
2
34
0
1
Order By: Relevance
“…To our knowledge, no previous fetal MR imaging studies have looked at lens growth. Achiron et al 9 in 1995 reported a linear growth pattern of the fetal lens circumference based on fetal sonography measurements. Goldstein et al 10 and Dilmen et al 13 described linear growth of the fetal lens diameter by prenatal sonography measurements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, no previous fetal MR imaging studies have looked at lens growth. Achiron et al 9 in 1995 reported a linear growth pattern of the fetal lens circumference based on fetal sonography measurements. Goldstein et al 10 and Dilmen et al 13 described linear growth of the fetal lens diameter by prenatal sonography measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Most ultrasonographic and postmortem autopsy studies have described a linear pattern of fetal eye and eye structure growth. [5][6][7][8][9][10][11][12][13] A few authors have suggested that exponential models of growth better suit the fetal eye, including the curve model by Jeanty et al, 17 which seem to be used most by obstetricians. 16,17 Many other studies in the literature were fitted to a linear growth curve, including another fetal MR imaging study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, these values can be useful for the estimation of gestational age. Prenatal evaluation of fetal orbit growth is superior for the early assessment of some facial and cranial abnormalities (3,4). Moreover, many morphological parameters that are revealed on USG in the second trimester of pregnancy are reported to be associated with genetic abnormalities (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Many facial anomalies such as retrognathia and a flat face are only recognizable in the profile view. Nomograms of the forehead, 9 orbits, 10,11 nose, 12,13 alveolar ridge, 14 mandible, 15 philtrum, 16 and chin 16,17 are available. However, there is a lack of studies that systematically describe craniofacial inclination of the fetal facial profile in the sagittal plane.…”
mentioning
confidence: 99%